Bacterial Infections across the Ants: Frequency and Prevalence of Wolbachia, Spiroplasma, and Asaia - Stefanie Kautz; Benjamin E. R. Rubin; Corrie S. Moreau (Psyche: A Journal of Entomology)
Bacterial endosymbionts are common across insects, but we often lack a deeper knowledge of their prevalence across most organisms. Next-generation sequencing approaches can characterize bacterial diversity associated with a host and at the same time facilitate the fast and simultaneous screening of infectious bacteria. In this study, we used 16S rRNA tag encoded amplicon pyrosequencing to survey bacterial communities of 310 samples representing 221 individuals, 176 colonies and 95 species of ants. We found three distinct endosymbiont groups—Wolbachia (Alphaproteobacteria: Rickettsiales), Spiroplasma (Firmicutes: Entomoplasmatales), and relatives of Asaia (Alphaproteobacteria: Rhodospirillales)—at different infection frequencies (at the ant species level: 22.1%, 28.4%, and 14.7%, resp.) and relative abundances within bacterial communities (1.0%–99.9%). Spiroplasma was particularly enriched in the ant genus Polyrhachis, while Asaia relatives were most prevalent in arboreal ants of the genus Pseudomyrmex. While Wolbachia and Spiroplasma have been surveyed in ants before, Asaia, an acetic acid bacterium capable of fixing atmospheric nitrogen, has received much less attention. Due to sporadic prevalence across all ant taxa investigated, we hypothesize facultative associations for all three bacterial genera. Infection patterns are discussed in relation to potential adaptation of specific bacteria in certain ant groups.